Prediction of treatment response in patients with locally advanced cervical cancer using midtreatment PET/MRI during concurrent chemoradiotherapy - Vojtíšek, Radovan; Baxa, Jan; Kovářová, Petra; Almortaza, Amira; Hošek, Petr; Sukovská, Emília; Tupý, Radek; Ferda, Jiří; Fínek, Jindřich (Strahlentherapie und Onkologie, 2021)
PURPOSE: We aimed to find metabolic, functional or morphological characteristics of the tumor predicting failure to achieve complete metabolic remission (CMR) by the midtreatment PET/MRI (positron emission tomography/magnetic resonance imaging) in cervical cancer patients. METHODS: We evaluated 66 patients treated between August 2015 and November 2019 who underwent pretreatment staging, subsequent midtreatment evaluation, and definitive restaging 3 months after completing the whole treatment, all using PET/MRI. The pretreatment parameters (pre-SUVmax, pre-SUVmean, pre-MTV, pre-MTV‑S, pre-TLG, pre-TLG‑S [SUV: standard uptake value, MTV: metabolic tumor volume, TLG: total lesion glycolysis]), and the midtreatment parameters at week 5 during chemoradiotherapy (mid-SUVmax, mid-SUVmean, mid-MTV, mid-MTV‑S, mid-TLG and mid-TLG-S) were recorded. The value of ADC (apparent diffusion coefficient) was also measured. Furthermore, we recorded absolute and relative changes in all parameters-∆ and ∆%. We divided the whole group of patients into "responders" (CMR) and "non-responders" (non-CMR), and compared them on the basis of the parameters from pre-PET/MRI and mid-PET/MRI. RESULTS: A statistically significant difference in the evaluated parameters between responders and non-responders was found for the following parameters: mid-MTV, mid-TLG, mid-TLG‑S, mid-MTV‑S, mid-tumor size, and ∆%SUVmax. According to the ROC (receiver operating characteristic) analysis, mid-MTV‑S showed the best albeit moderate discrimination ability for the prediction of non-CMR. Significant mutual correlations of all variables, in particular between mid-MTV‑S and mid-TLG‑S and between mid-MTV and mid-TLG, were found (all p < 0.05). CONCLUSION: Our study confirmed that when using the midtreatment PET/MRI we are able to identify metabolic parameters having the discrimination ability for the prediction of non-CMR. In particular mid-MTV‑S, mid-MTV, mid-tumor size, mid-TLG‑S, mid-TLG and ∆%SUVmax.
Keywords: dospělí; Magnetic Resonance Imaging; Carcinoma, Squamous Cell; tumor burden; Antineoplastic Agents, Alkylating; cisplatina; Female; Multimodal Imaging; ozařování lymfatického systému; Lymphatic Metastasis; lymfatické metastázy; Adult; výsledek terapie; ženské pohlaví; Cisplatin; lidé; Tumor Burden; staging nádorů; magnetická rezonanční tomografie; Lymphatic Irradiation; Treatment Outcome; nádory děložního čípku; prognóza; ROC křivka; Humans; Brachytherapy; počítačové zpracování obrazu; Aged; spinocelulární karcinom; brachyterapie; chemoradioterapie; Prognosis; Uterine Cervical Neoplasms; lidé středního věku; plocha pod křivkou; multimodální zobrazování; pozitronová emisní tomografie; senioři; radioterapie s modulovanou intenzitou; alkylační protinádorové látky; Middle Aged; Neoplasm Staging; Chemoradiotherapy; Radiotherapy, Intensity-Modulated; Positron-Emission Tomography; Image Processing, Computer-Assisted; ROC Curve; Area Under Curve